Alterations in Adipose Tissue and Adipokines in Heterozygous APE1/Ref-1 Deficient Mice - Eun-Ok Lee; Hao Jin; Sungmin Kim; Hee Kyoung Joo; Yu Ran Lee; Soo Yeon An; Shuyu Piao; Kwon Ho Lee; Byeong Hwa Jeon (Endocrinology and Metabolism)
Background The role of apurinic/apyrimidinic endonuclease 1/redox factor-1 (APE1/Ref-1) in adipose tissue remains poorly understood. This study investigates adipose tissue dysfunction in heterozygous APE1/Ref-1 deficiency (APE1/Ref-1+/-) mice, focusing on changes in adipocyte physiology, oxidative stress, adipokine regulation, and adipose tissue distribution. Methods APE1/Ref-1 mRNA and protein levels in white adipose tissue (WAT) were measured in APE1/Ref-1+/- mice, compared to their wild-type (APE1/Ref-1+/+) controls. Oxidative stress was assessed by evaluating reactive oxygen species (ROS) levels. Histological and immunohistochemical analyses were conducted to observe adipocyte size and macrophage infiltration of WAT. Adipokine expression was measured, and micro-magnetic resonance imaging (MRI) was used to quantify abdominal fat volumes. Results APE1/Ref-1+/- mice exhibited significant reductions in APE1/Ref-1 mRNA and protein levels in WAT and liver tissue. These mice also showed elevated ROS levels, suggesting a regulatory role for APE1/Ref-1 in oxidative stress in WAT and liver. Histological and immunohistochemical analyses revealed hypertrophic adipocytes and macrophage infiltration in WAT, while Oil Red O staining demonstrated enhanced ectopic fat deposition in the liver of APE1/Ref-1+/- mice. These mice also displayed altered adipokine expression, with decreased adiponectin and increased leptin levels in the WAT, along with corresponding alterations in plasma levels. Despite no significant changes in overall body weight, microMRI assessments demonstrated a significant increase in visceral and subcutaneous abdominal fat volumes in APE1/Ref-1+/- mice. Conclusion APE1/Ref-1 is crucial in adipokine regulation and mitigating oxidative stress. These findings suggest its involvement in adipose tissue dysfunction, highlighting its potential impact on abdominal fat distribution and its implications for obesity and oxidative stress-related conditions.